2003
DOI: 10.1897/1551-5028(2003)022<1017:irbbfa>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Relationship Between Bioconcentration Factor and Exposure Concentration for Metals: Implications for Hazard Assessment of Metals in the Aquatic Environment

Abstract: The bioconcentration factor (BCF) and bioaccumulation factor (BAF) are used as the criteria for bioaccumulation in the context of identifying and classifying substances that are hazardous to the aquatic environment. The BCF/BAF criteria, while developed as surrogates for chronic toxicity and/or biomagnification of anthropogenic organic substances, are applied to all substances including metals. This work examines the theoretical and experimental basis for the use of BCF/BAF in the hazard assessment of Zn, Cd, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
48
2
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 99 publications
(138 reference statements)
10
48
2
2
Order By: Relevance
“…Though the data suggest a curvilinear rather than linear relationship, we chose to use the linear relationship because it provides a more environmentally protective description of the water-to-tissue relationship. The GSL Se data (Table 5) also demonstrate an inverse relationship between waterborne exposure concentration and corresponding bioaccumulation factor that is frequently observed for metals [36,37].…”
Section: Bioaccumulation Studysupporting
confidence: 53%
“…Though the data suggest a curvilinear rather than linear relationship, we chose to use the linear relationship because it provides a more environmentally protective description of the water-to-tissue relationship. The GSL Se data (Table 5) also demonstrate an inverse relationship between waterborne exposure concentration and corresponding bioaccumulation factor that is frequently observed for metals [36,37].…”
Section: Bioaccumulation Studysupporting
confidence: 53%
“…In the present study, a significant negative correlation was also found for Cd (p < 0.001) and Zn (p < 0.05) but not for Cu at the level of whole body (Figure 4). Such an inverse relationship between the TTF and the metal concentration in a purified diet is analogous to the relationship found between the bioconcentration factor and the metal concentration in the water [20,59] and has important implications for environmental evaluations such as classifying hazards and assessing ecological risks. Because higher TTFs were associated with lower metal burdens in prey, TTF should not be used to indicate the bioaccumulation or trophic transfer (bioavailability) without considering the exposure concentration.…”
Section: Metal Concentration Dependent Trophic Transfermentioning
confidence: 69%
“…It follows that any water quality guidelines seeking to protect biota from deleterious effects of Tl should consider the role of K. The Tl(I) concentrations used in the uptake experiments described here (2.75 nM) exceed Tl concentrations observed in the Great Lakes (6-180 pM). Because concentration factors for some metals in aquatic organisms can be inversely related to ambient metal concentrations [26], the concentration factors reported here for Tl in phytoplankton may be underestimates. However, concentration factors on dry weight bases, determined with Tl(I) additions of 1 nM to Lakes Erie and Ontario seston, were about 1 ϫ 10 3 [7], suggesting that the concentration factors determined in the experiments reported here probably are not underestimates of the degree of enrichment of this element in natural phytoplankton communities.…”
Section: Role Of K In Tl(i) and Dmt Uptake Thallium(i) Uptake Bymentioning
confidence: 82%